Census of Urban Crime, 1970 - Hellman, Daryl A. ([Verlag nicht ermittelbar], 1985)
This data collection contains information on urban crime in the United States. The 331 variables include crime incidence, criminal sanctions, police employment, police expenditures, police unionization, city revenues and sources of revenue (including intergovernmental transfers), property values, public sector package characteristics, demographic and socioeconomic characteristics, and housing and land use characteristics. The data were primarily gathered from various governmental censuses: Census of Population, Census of Housing, Census of Government, Census of Manufactures, and Census of Business. UNIFORM CRIME REPORTING PROGRAM DATA [UNITED STATES] (ICPSR 9028) and EXPENDITURE AND EMPLOYMENT DATA FOR THE CRIMINAL JUSTICE SYSTEM (ICPSR 7818) were used as supplemental sources.